205k views
4 votes
Which expression can be used to find the value of expression below -(7/10) + 2/8 + 1/10 - (4/8)

User Inye
by
5.7k points

1 Answer

5 votes

Answer:

(-17)/20

Explanation:

Simplify the following:

-7/10 + 2/8 + 1/10 - 4/8

The gcd of 2 and 8 is 2, so 2/8 = (2×1)/(2×4) = 2/2×1/4 = 1/4:

-7/10 + 1/4 + 1/10 - 4/8

The gcd of -4 and 8 is 4, so (-4)/8 = (4 (-1))/(4×2) = 4/4×(-1)/2 = (-1)/2:

-7/10 + 1/4 + 1/10 + -1/2

Put -7/10 + 1/4 + 1/10 - 1/2 over the common denominator 20. -7/10 + 1/4 + 1/10 - 1/2 = (2 (-7))/20 + 5/20 + 2/20 - 10/20:

(2 (-7))/20 + 5/20 + 2/20 - 10/20

2 (-7) = -14:

(-14)/20 + 5/20 + 2/20 - 10/20

-14/20 + 5/20 + 2/20 - 10/20 = (-14 + 5 + 2 - 10)/20:

(-14 + 5 + 2 - 10)/20

-14 + 5 + 2 - 10 = (5 + 2) - (14 + 10):

((5 + 2) - (14 + 10))/20

5 + 2 = 7:

(7 - (14 + 10))/20

| 1 | 4

+ | 1 | 0

| 2 | 4:

(7 - 24)/20

7 - 24 = -(24 - 7):

(-(24 - 7))/20

| 1 | 14

| 2 | 4

- | | 7

| 1 | 7:

Answer: (-17)/20

User Drevak
by
5.5k points